Agent-Based Modeling to Strengthen Entrepreneurial Competitiveness and Productivity of Non-Urban SMEs in Indonesia - Supriadi, Iman; Yulfajar, Amrina; Wibowo , Nugroho (Business Innovation Management and Entrepreneurship Journal (BIMANTARA), 2026)
Small and Medium Enterprises (SMEs) play a critical role in Indonesia’s economic structure; however, their productivity, particularly in non-urban areas, remains constrained by institutional inefficiencies and regulatory burdens. This study examines the causal dynamics between bureaucratic efficiency, regulatory burden, and SME productivity while accounting for spatial differences between urban and non-urban contexts. To address this issue, an Agent-Based Modeling (ABM) approach is employed to simulate heterogeneous SME agents that interact adaptively within varying institutional environments. Scenario-based simulations enable the analysis of non-linear and emergent outcomes resulting from micro-level entrepreneurial behavior and institutional constraints. The findings demonstrate that improvements in bureaucratic efficiency significantly increase average SME profits and overall system productivity, whereas moderate variations in regulatory burden have limited direct effects on production levels. In addition, non-urban SMEs exhibit relatively more stable profit trajectories than urban SMEs, reflecting adaptive advantages related to cost structures and local institutional flexibility. The study concludes that bureaucratic efficiency represents a strategic policy lever for enhancing SME competitiveness, and that productivity growth in non-urban regions requires policy interventions that emphasize institutional reform alongside conventional economic support measures.